Ship accessory antirust coating and preparation method thereof
Through the multi-layer coating structure of nanoceramics and rare earth oxide composite layer and Cu@SiO2 core-shell particles anti-fouling surface, the problems of corrosion and biological adhesion of ship coatings in the marine environment are solved, and efficient anti-corrosion, anti-fouling and self-repair are achieved, reducing construction time and maintenance costs.
Patent Information
- Application Number
- CN202510602160.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-12
- Publication Date
- 2025-08-12
- Estimated Expiration
- 2045-05-12
AI Technical Summary
The existing marine coatings are prone to corrosion, biological adhesion and mechanical impact in high salinity and high humidity marine environments, and have low construction efficiency, making it difficult to meet the needs of durability and rapid maintenance at the same time.
The basic corrosion-resistant layer combined with nanoceramics and rare earth oxides is adopted, combined with Cu@SiO2 core-shell particles anti-fouling surface layer and self-healing microcapsules, and through light/thermal collaborative curing technology, a multi-layer coating structure is formed to enhance anti-corrosion, anti-fouling and self-healing performance.
It significantly improves the durability and anti-fouling effect of the coating, extends the service life to more than 5 years, reduces construction costs and maintenance frequency, and improves mechanical performance and environmental adaptability.
Smart Images

Figure BDA0005397125980000091 
Figure BDA0005397125980000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ship protection materials, and in particular to an anti-rust coating for ship accessories and a preparation method thereof. Background Art
[0002] Ships are exposed to harsh marine environments with high salinity, high humidity, and alternating wet and dry conditions for a long time. Their protective coatings must simultaneously meet multiple requirements, including corrosion resistance, anti-biological adhesion, mechanical shock resistance, and rapid maintenance. However, existing coating technologies have significant limitations:
[0003] Although traditional epoxy resin coatings have good adhesion and chemical stability, they are prone to blistering and peeling under long-term salt spray (ASTMB117) conditions, especially in tropical waters. Their actual service life is usually less than 5 years, requiring frequent repairs, increasing maintenance costs.
[0004] While copper-based antifouling coatings (such as cuprous oxide or copper powder) can effectively inhibit the attachment of marine organisms, they are susceptible to corrosion when in direct contact with seawater, leading to interfacial delamination and accelerated coating failure. Existing solutions (such as insulating layers) often sacrifice antifouling or anticorrosion performance.
[0005] The substrate surface treatment is usually required to reach Sa2.5 level (ISO 8501), but due to limited conditions at the ship repair site, it can only reach Sa2 level (local residual rust), making it difficult to repair in time.
[0006] Traditional heat-curing coatings require over 72 hours to reach full strength, significantly extending the ship's dry docking period (with daily costs exceeding $100,000). While light-curing technology has been tried, it struggles to achieve both deep curing and balanced performance for thick coatings (>200μm). Summary of the Invention
[0007] In response to the shortcomings of the existing technology, the present invention provides a multifunctional ship coating with long-term anti-corrosion, anti-biological attachment, self-repair and fire-resistant properties and a preparation method thereof, which is suitable for harsh environments such as hulls, ballast tanks, and decks.
[0008] According to a first aspect of the present invention, there is provided an anti-rust coating for ship fittings, comprising the following three layers and components from the inside to the outside:
[0009] Basic corrosion-resistant layer: by mass, including:
[0010] 10-30 parts of nano-ceramic material, selected from at least one of Al2O3, SiO2 or ZrO2, to form a dense physical barrier to block Cl - , H2O and other corrosive media penetration (permeability reduced by more than 60%), nanoparticles fill the coating micropores and improve the hardness (pencil hardness ≥ 4H);
[0011] 5-15 parts of rare earth oxide, at least one selected from CeO2, La2O3 or Y2O3, Ce 3+ / Ce 4+ The redox reaction passivates the steel substrate, forming a Ce(OH)3 / CeO2 protective film, and La2O3 adsorbs SO4 2- Acidic ions inhibit local acid corrosion;
[0012] 0.5-1.5 parts of amino-modified graphene oxide (GO-NH2), -NH2 forms hydrogen bonds with -CF2- of fluorocarbon resin, enhancing interfacial bonding strength, and the conductive network dissipates static electricity, thus avoiding local charge accumulation leading to coating peeling;
[0013] 40-60 parts of fluorocarbon resin, selected from polyvinylidene fluoride (PVDF) or fluoroethylene-vinyl ether copolymer (FEVE);
[0014] Epoxy-polyurethane hybrid resin, 20-30 parts;
[0015] 3 to 8 parts of zinc phosphate corrosion inhibitor, zinc phosphate (Zn3(PO4)2) forms a passivation film in the repair area to prevent secondary corrosion;
[0016] 2-5 self-healing microcapsules, containing a dicyclopentadiene (DCPD) core material and a polyurea formaldehyde (PUF) wall material. After the capsule ruptures, the DCPD polymerizes with the residual Grubbs catalyst to fill the cracks, while the PUF wall material slowly releases a repair agent, suitable for Sa2-grade surfaces (containing trace rust);
[0017] 1 to 3 parts of a photoinitiator, selected from 2-hydroxy-2-methyl-1-phenyl-1-propanone (HMPP) or benzophenone.
[0018] After co-grinding rare earth oxides with nanoceramics, the rare earth particles disperse within the ceramic network, filling the nanoceramic's pores with rare earth particles, further reducing porosity and providing a wider passivation coverage, increasing the Ce content on the substrate surface by three times. The amino-modified graphene oxide and nanoceramics together create a three-dimensional "ceramic-graphene" framework, increasing compressive strength to 120 MPa (compared to 80 MPa for pure resin).
[0019] Interface transition layer: by mass, including:
[0020] 3-5 parts of γ-aminopropyltriethoxysilane (KH-550);
[0021] 2 to 5 parts of organic silicone resin coated copper powder (Cu@SiO2), with a copper content of ≥60wt%.
[0022] -NH2 bonds with the hydroxyl groups of the underlying rare earth oxide, -OCH3 condenses with the surface silicone resin, and when used with Cu@SiO2 core-shell particles, the SiO2 shell and KH-550 form a Si-O-Si network, and the interface resistance is increased to 10 12 Ω (to avoid galvanic corrosion). The SiO2 shell isolates copper from the underlying rare earth oxide, preventing Cu 2+ Initiate redox reaction, copper core slowly releases Cu + / Cu 2+ , maintain the anti-fouling effect.
[0023] Antifouling surface layer: by mass, including:
[0024] 10-15 parts of Cu@SiO2 core-shell particles;
[0025] 10-15 parts of polydimethylsiloxane and methyltrimethoxysilane copolymer (PDMS-MTMOS copolymer);
[0026] 1 to 3 parts of antifouling aid, at least one selected from capsaicin or zinc pyrithione (ZPT).
[0027] PDMS resin encapsulates Cu@SiO2, creating a dual antifouling mechanism combining low surface energy (contact angle 112°) and ion release. The PDMS-MTMOS copolymer's low surface energy (≤25mN / m) makes it difficult for organisms to attach, while MTMOS crosslinking enhances mechanical strength. When combined with capsaicin / ZPT, the surface energy is further reduced to 20mN / m, and ZPT inhibits microbial biofilm formation. Capsaicin interferes with nerve conduction in barnacle larvae, while ZPT disrupts algal cell membranes, resulting in a broad-spectrum antifouling effect: 95% algae inhibition and 90% barnacle inhibition. Combined with Cu@SiO2, the antifouling effect is extended to 5 years (compared to 3 years for copper-based coatings alone).
[0028] A KH-550 transition layer isolates the rare earth oxide (base) from the Cu@SiO2 (surface) layer, while maintaining dual protection. A graphene-reinforced ceramic skeleton provides mechanical support, while microcapsules repair localized damage, increasing overall lifespan by three times. The hydrophobicity of the fluorocarbon resin (contact angle of 105°) reduces water retention, while the PDMS surface layer inhibits bioattachment, synergistically reducing the risk of corrosion.
[0029] According to an embodiment of the present invention, the particle size of the nano-ceramic material is 20 to 100 nm;
[0030] The mass ratio of the nano-ceramic material to the rare earth oxide is 2:1 to 3:1;
[0031] The oxygen content of the amino-treated graphene oxide is less than or equal to 10 wt %.
[0032] According to an embodiment of the present invention, the particle size of the self-repairing microcapsule is 10-50 μm, and the thickness of the wall material accounts for 10%-15% of the total mass of the capsule.
[0033] According to an embodiment of the present invention, the basic corrosion-resistant layer further comprises 0.1 to 0.5 parts of carbon nanotubes for enhancing electrical conductivity.
[0034] According to an embodiment of the present invention, the thickness of the interface transition layer is 5 to 10 μm, and the molar ratio of the γ-aminopropyltriethoxysilane to the hydroxyl group on the surface of the rare earth oxide is 1:1 to 1.2.
[0035] According to an embodiment of the present invention, the antifouling agent is a complex of capsaicin and ZPT, with a mass ratio of 1:1 to 1:2.
[0036] According to an embodiment of the present invention, the copper core of the Cu@SiO2 core-shell particles has a diameter of 1 to 5 μm and a SiO2 shell thickness of 100 to 300 nm;
[0037] The copper content of the silicone resin coated copper powder is ≥60 wt %.
[0038] According to an embodiment of the present invention, the curing method of the basic corrosion-resistant layer is ultraviolet curing, and the energy density is 300-500mJ / cm 2 .
[0039] According to a second aspect of the present invention, there is provided a method for preparing an anti-rust coating for ship accessories, comprising the following steps:
[0040] Preparation of basic corrosion-resistant layer:
[0041] The nano-ceramic material and the rare earth oxide were added into a ball mill, and anhydrous ethanol was added in an amount of 50% of the total weight of the nano-ceramic material and the rare earth oxide. Zirconia balls were used as the grinding medium (ball-to-material ratio 5:1). After ball milling, the mixture was vacuum dried (60° C., 2 hours) to obtain a uniform composite powder.
[0042] Ball milling parameters: speed 300-400 rpm, time 2-4 hours, temperature 25-30°C;
[0043] Add fluorocarbon resin and epoxy-polyurethane hybrid resin into the reactor and stir until the viscosity of the system is stable;
[0044] Add a photoinitiator and continue stirring for 30 minutes to obtain a resin matrix;
[0045] Stirring parameters: 60-80°C, rotation speed 200-300 rpm, time 1-2 hours, until the system viscosity stabilizes (Brookfield viscometer, 2000-3000 cP at 25°C);
[0046] The composite powder and zinc phosphate corrosion inhibitor were added to the resin matrix, and after high-speed dispersion (1000-1500 rpm, 30 minutes), amino-modified graphene oxide was added and ultrasonic treatment was performed (power 500 W, frequency 40 kHz, 30 minutes);
[0047] Finally, the self-repairing microcapsules were added and stirred at a low speed (100 rpm, 15 min) to avoid capsule rupture to obtain a mixed slurry;
[0048] Spray the mixed slurry onto the surface of the ship substrate (spray gun pressure 0.3-0.5 MPa, distance 20-30 cm); let it stand at 50°C for 10-15 minutes to allow the solvent to evaporate, thereby obtaining a basic corrosion-resistant layer;
[0049] Preparation of interface transition layer:
[0050] γ-Aminopropyltriethoxysilane was dissolved in ethanol (concentration 5 wt%) and sprayed onto the basic corrosion-resistant layer; curing parameters: reaction at room temperature (25° C.) for 30 minutes to form a chemically bonded interface.
[0051] Copper powder was mixed with silicone resin, ultrasonically dispersed for 20 minutes, sprayed onto the chemical bonding interface, and cured to obtain the interface transition layer (wet film thickness 10-15 μm); curing parameters: 80° C.±2° C., time 1 hour.
[0052] Antifouling surface preparation:
[0053] Cu@SiO2 core-shell particles, polydimethylsiloxane and methyltrimethoxysilane copolymer, and antifouling agent were mixed, xylene solvent (solid content 40 wt%) was added, and ball milling was performed for 2 hours (rotation speed 200 rpm) to obtain antifouling slurry.
[0054] The antifouling slurry is applied to the interface transition layer by a roller coating process (roller speed 5-10 m / min);
[0055] Curing parameters: Curing at room temperature (25℃) for 24 hours, or accelerated curing at 60℃ for 2 hours.
[0056] Light / heat synergistic curing:
[0057] UV curing with a wavelength of 365nm and an energy density of 300-500mJ / cm 2 , exposure time 30 to 60 seconds;
[0058] The anti-rust coating for the ship accessories is obtained by thermal curing at 80° C. for 1 hour.
[0059] According to an embodiment of the present invention, the method for preparing the self-repairing microcapsule includes:
[0060] Dicyclopentadiene was mixed with 1 wt% of the dicyclopentadiene emulsifier Span-80, and deionized water was added to obtain a water-to-oil ratio of 3:1;
[0061] High-speed shear emulsification (10,000-12,000 rpm, 10 minutes) to form a water-in-oil emulsion with a droplet size of 10-50 μm;
[0062] Urea and formaldehyde were added to the water-in-oil emulsion at a molar ratio of 1:1.5, and the pH was adjusted to 3.5-4.0 (using a 10% citric acid solution). The reaction parameters were: 60°C ± 2°C, stirring speed 300 rpm, and reaction time 4 hours. After the reaction was completed, the pH was adjusted to 7.0 with a NaOH solution to terminate the reaction, and the microcapsules were filtered to obtain microcapsules.
[0063] The microcapsules were washed with deionized water for three times and vacuum dried at 40° C. for 6 hours to obtain the self-repairing microcapsules.
[0064] The multifunctional protective coating for ships provided by the present invention achieves a comprehensive improvement in anti-corrosion, anti-fouling, self-repair and construction efficiency through the synergistic effect of multiple components, demonstrating significant technological progress and practical value. In terms of anti-corrosion performance, the composite system of nano-ceramics and rare earth oxides constructs a dense physical and chemical barrier, which enables the coating to remain intact during a 3,000-hour salt spray test, which is more than three times longer than the life of traditional coatings. The introduction of graphene not only enhances the adhesion of the coating (reaching the highest level 5B), but also eliminates the risk of static electricity accumulation through a conductive network. In conjunction with the self-repairing microcapsule system, it can achieve a damage repair rate of more than 88% at 40°C, significantly improving the durability and ease of maintenance of the coating.
[0065] In terms of antifouling performance, the innovative Cu@SiO2 core-shell structure combined with the PDMS low-surface-energy coating avoids the galvanic corrosion issues associated with traditional copper-based coatings and anti-corrosion layers. Through a dual mechanism of slow-release copper ions and physical repulsion, it achieves a long-lasting antifouling effect lasting over five years, limiting the area of marine biofouling to less than 5%. A specially designed interfacial transition layer, through chemical bonding, tightly binds the different functional coatings, increasing the peel strength to 4.8 MPa and ensuring the coating system's stability in complex marine environments.
[0066] In terms of construction technology, the application of light / heat synergistic curing technology shortens the traditional 72-hour curing time to less than 24 hours. Combined with its adaptability to low surface treatment conditions (Sa2 level), it increases coating construction efficiency by over 50%, significantly reducing docking costs for ship repairs. Comprehensive testing has shown that this coating system excels in mechanical properties (compressive strength of 120MPa), fire resistance (passing the SOLAS A60 standard), and environmental adaptability (stable from -40°C to 120°C), providing a comprehensive solution for ship protection with significant economic benefits and market application prospects. DETAILED DESCRIPTION
[0067] The present application provides an anti-rust coating for ship accessories and a preparation method thereof.
[0068] Example 1
[0069] Basic corrosion resistant layer:
[0070] Nano ceramic material (Al2O3): 20 parts
[0071] Rare earth oxide (CeO2): 10 parts
[0072] Amination of graphene oxide: 1 part
[0073] Fluorocarbon resin (polyvinylidene fluoride): 50 parts
[0074] Epoxy-polyurethane hybrid resin: 25 parts
[0075] Zinc phosphate corrosion inhibitor: 5 parts
[0076] Self-repairing microcapsules (dicyclopentadiene core material and polyurea formaldehyde wall material): 3 parts
[0077] Photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone): 2 parts
[0078] Interface transition layer:
[0079] γ-aminopropyltriethoxysilane: 4 parts
[0080] Silicone resin coated copper powder: 3 parts
[0081] Antifouling surface:
[0082] Cu@SiO2 core-shell particles: 12 parts
[0083] Polydimethylsiloxane and methyltrimethoxysilane copolymer: 12 parts
[0084] Antifouling agent (capsaicin): 1.5 parts
[0085] Example 2
[0086] Basic corrosion-resistant layer: nano-ceramic material (ZrO2): 30 parts; other ingredients are the same as in Example 1.
[0087] Interface transition layer and antifouling surface layer: same as in Example 1.
[0088] Example 3
[0089] Basic corrosion-resistant layer: 1.5 parts of amino-treated graphene oxide; other ingredients are the same as in Example 1.
[0090] Interface transition layer and antifouling surface layer: same as in Example 1.
[0091] Example 4
[0092] Basic corrosion-resistant layer: self-repairing microcapsules: 5 parts; other ingredients are the same as in Example 1.
[0093] Interface transition layer and antifouling surface layer: same as in Example 1.
[0094] Example 5
[0095] Basic corrosion-resistant layer: add 0.3 parts of carbon nanotubes; other ingredients are the same as in Example 1.
[0096] Interface transition layer and antifouling surface layer: same as in Example 1.
[0097] Example 6
[0098] Basic corrosion-resistant layer: zinc phosphate corrosion inhibitor: 8 parts; other ingredients are the same as in Example 1.
[0099] Interface transition layer and antifouling surface layer: same as in Example 1.
[0100] Comparative Example
[0101] Comparative Example 1
[0102] Basic corrosion-resistant layer: no self-repairing microcapsules are added; other components are the same as in Example 1.
[0103] Interface transition layer and antifouling surface layer: same as in Example 1.
[0104] Comparative Example 2
[0105] Basic corrosion-resistant layer: ordinary graphene is used instead of amino-treated graphene oxide: 1 part; other ingredients are the same as in Example 1.
[0106] Interface transition layer and antifouling surface layer: same as in Example 1.
[0107] Comparative Example 3
[0108] Basic corrosion-resistant layer and antifouling surface layer: direct bonding without the use of interface transition layer.
[0109] The specific components of the basic corrosion-resistant layer and the antifouling surface layer are the same as those in Example 1.
[0110] Comparative Example 4
[0111] Antifouling surface layer: No antifouling agent is used; other ingredients are the same as in Example 1.
[0112] Basic corrosion-resistant layer and interface transition layer: same as in Example 1.
[0113] Experimental example
[0114] Salt spray test
[0115] According to ISO 9227, samples coated with different formulations were placed in a salt spray chamber and exposed to a 5% NaCl solution spray environment for 3000 hours. The surface condition of the coating was observed and recorded.
[0116] Adhesion test
[0117] The pull-off test is performed according to ISO 4624, using a tensile testing machine to measure the force required to peel the coating from the substrate. The test is then graded (0B to 5B) according to ASTM D3359.
[0118] Self-repair efficiency test
[0119] Scratches were created on the coating surface, and then the coating was placed at 40°C to observe the repair process. The self-repair efficiency was evaluated by calculating the ratio of the repaired damage area to the original damage area.
[0120] Antifouling performance test
[0121] The samples coated with coatings of different formulations were placed in the marine environment, and the area of marine organism attachment was regularly inspected and recorded, expressed as a percentage.
[0122] Peel strength test
[0123] The peel strength between the coating and the substrate was measured using the adhesive tape method using ASTM D3359, and the unit is MPa.
[0124] Curing time test
[0125] The time required for the coating to be fully cured from application was monitored, and the specific time required for curing to be completed was recorded. The results are shown in Table 1.
[0126] Table 1. Performance test results of Examples 1-6 and Comparative Examples 1-4
[0127]
[0128]
[0129] Data Analysis and Conclusion
[0130] Salt spray test: The examples show good corrosion resistance, while comparative examples 1 and 2 show different degrees of damage.
[0131] Adhesion test: The examples showed excellent overall performance, reaching the highest level of 5B; while the comparative examples showed decreased adhesion due to the lack of certain key components.
[0132] Self-repairing efficiency: The self-repairing microcapsules in the examples significantly improved the self-repairing ability of the coating. In contrast, the self-repairing efficiency of Comparative Example 1 was low due to the lack of self-repairing microcapsules.
[0133] Antifouling performance test: The combination of the Cu@SiO2 core-shell structure and the PDMS low surface energy coating effectively reduced the attachment area of marine organisms. Comparative Example 4 did not add antifouling additives, resulting in an increase in the attachment area of marine organisms.
[0134] Peel strength test: The presence of the interface transition layer greatly enhances the overall peel strength of the coating. Comparative Example 3 has a lower peel strength due to the lack of this layer.
[0135] Curing time test: The light / heat synergistic curing technology of each component significantly shortens the curing time, and all samples can be cured within 24 hours.
[0136] in conclusion
[0137] The multifunctional protective coating for ships provided by the present invention achieves a comprehensive improvement in anti-corrosion, anti-fouling, self-repair and construction efficiency through the synergistic effect of multiple components, demonstrating significant technological progress and practical value. In terms of anti-corrosion performance, the composite system of nano-ceramics and rare earth oxides constructs a dense physical and chemical barrier, which enables the coating to remain intact during a 3,000-hour salt spray test, which is more than three times longer than the life of traditional coatings. The introduction of graphene not only enhances the adhesion of the coating (reaching the highest level 5B), but also eliminates the risk of static electricity accumulation through a conductive network. In conjunction with the self-repairing microcapsule system, it can achieve a damage repair rate of more than 88% at 40°C, significantly improving the durability and ease of maintenance of the coating.
[0138] Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0139] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if such changes and modifications fall within the scope of the claims and their equivalents, the present invention is intended to include such changes and modifications.
Claims
1. A rust-proof coating for ship accessories, characterized in that: From the inside to the outside, it includes the following three layers of structure and components: Basic corrosion-resistant layer: by mass, including: 10-30 parts of nano-ceramic material, at least one selected from Al2O3, SiO2 or ZrO2; 5-15 parts of rare earth oxide, at least one selected from CeO2, La2O3 or Y2O3; Aminated graphene oxide, 0.5-1.5 parts; 40-60 parts of fluorocarbon resin selected from polyvinylidene fluoride or vinyl fluoride-vinyl ether copolymer; Epoxy-polyurethane hybrid resin, 20-30 parts; 3-8 parts of zinc phosphate corrosion inhibitor; 2 to 5 parts of self-repairing microcapsules, comprising a dicyclopentadiene core material and a polyurea formaldehyde wall material; 1 to 3 parts of a photoinitiator selected from 2-hydroxy-2-methyl-1-phenyl-1-propanone or benzophenone; Interface transition layer: by mass, including: γ-aminopropyltriethoxysilane, 3-5 parts; Silicone resin coated copper powder, 2-5 parts; Antifouling surface layer: by mass, including: Cu@SiO2 core-shell particles, 10-15 parts; 10-15 parts of polydimethylsiloxane and methyltrimethoxysilane copolymer; 1 to 3 parts of antifouling aid, at least one selected from capsaicin or zinc pyrithione.
2. The anti-rust coating for ship accessories according to claim 1, characterized in that: The particle size of the nano-ceramic material is 20 to 100 nm; The mass ratio of the nano-ceramic material to the rare earth oxide is 2:1 to 3:1; The oxygen content of the amino-treated graphene oxide is less than or equal to 10 wt %.
3. The anti-rust coating for ship accessories according to claim 1, characterized in that: The particle size of the self-repairing microcapsule is 10-50 μm, and the thickness of the wall material accounts for 10%-15% of the total mass of the capsule.
4. The anti-rust coating for ship accessories according to claim 1, characterized in that: The basic corrosion-resistant layer also contains 0.1 to 0.5 parts of carbon nanotubes for enhancing electrical conductivity.
5. The anti-rust coating for ship accessories according to claim 1, characterized in that: The thickness of the interface transition layer is 5 to 10 μm, and the molar ratio of the gamma-aminopropyltriethoxysilane to the hydroxyl group on the surface of the rare earth oxide is 1:1 to 1.
2.
6. The method for preparing the anti-rust coating for ship accessories according to claim 1, characterized in that: The antifouling auxiliary agent is a compound of capsaicin and ZPT, with a mass ratio of 1:1 to 1:
2.
7. The method for preparing an anti-rust coating for ship accessories according to claim 1, characterized in that: The copper core of the Cu@SiO2 core-shell particles has a diameter of 1 to 5 μm and a SiO2 shell thickness of 100 to 300 nm; The copper content of the silicone resin coated copper powder is ≥60 wt %.
8. The method for preparing an anti-rust coating for ship accessories according to claim 1, characterized in that: The curing method of the basic corrosion-resistant layer is ultraviolet curing, and the energy density is 300-500mJ / cm 2 .
9. A method for preparing an anti-rust coating for ship accessories according to any one of claims 1 to 8, characterized in that: The steps include: Preparation of basic corrosion-resistant layer: Add nano-ceramic material and rare earth oxide into a ball mill, add anhydrous ethanol in an amount of 50% of the total weight of the nano-ceramic material and the rare earth oxide, use zirconium oxide balls as grinding media, and vacuum dry after ball milling to obtain a uniform composite powder; Add fluorocarbon resin and epoxy-polyurethane hybrid resin into a reaction kettle, stir until the viscosity of the system is stable, add photoinitiator, and continue stirring for 30 minutes to obtain a resin matrix; The composite powder and zinc phosphate corrosion inhibitor are added to the resin matrix, dispersed at high speed, and then amino-treated graphene oxide is added, followed by ultrasonic treatment; Finally, the self-repairing microcapsules were added and stirred at a low speed to avoid capsule rupture to obtain a mixed slurry; Spraying the mixed slurry onto the surface of the ship substrate; Standing at 50° C. for 10 to 15 minutes to evaporate the solvent, thereby obtaining the basic corrosion-resistant layer; Preparation of interface transition layer: Dissolving γ-aminopropyltriethoxysilane in ethanol and spraying the solution onto the surface of the base corrosion-resistant layer to form a chemically bonded interface; Mixing copper powder and silicone resin, ultrasonically dispersing for 20 minutes, spraying onto the chemical bonding interface, and curing to obtain the interface transition layer; Antifouling surface preparation: Cu@SiO2 core-shell particles, polydimethylsiloxane and methyltrimethoxysilane copolymer, and antifouling agent were mixed, xylene solvent was added, and ball milling was performed for 2 hours to obtain antifouling slurry; The antifouling slurry is applied to the interface transition layer by a roller coating process, and cured to obtain the antifouling surface layer; Light / heat synergistic curing: UV curing with a wavelength of 365nm and an energy density of 300-500mJ / cm 2 , exposure time 30 to 60 seconds; The anti-rust coating for the ship accessories is obtained by thermal curing at 80° C. for 1 hour.
10. The method for preparing an anti-rust coating for ship accessories according to claim 1, characterized in that: The preparation method of the self-repairing microcapsule comprises: Dicyclopentadiene was mixed with 1 wt% of the dicyclopentadiene emulsifier Span-80, and deionized water was added to obtain a water-to-oil ratio of 3:1; High-speed shear emulsification to form a water-in-oil emulsion with a droplet size of 10 to 50 μm; Adding urea and formaldehyde to the water-in-oil emulsion at a molar ratio of 1:1.5, adjusting the pH to 3.5-4.0, and after the reaction is completed, adjusting the pH to 7.0 with a NaOH solution to terminate the reaction, and filtering to obtain microcapsules; The microcapsules were washed with deionized water for three times and vacuum dried at 40° C. for 6 hours to obtain the self-repairing microcapsules.
Citation Information
Patent Citations
Graphene fluorocarbon long-acting protective thin finish paint and preparation method thereof
CN107353759A
Antifouling paint composition for ships and preparation method thereof
CN116694156A
Transferable wear-resistant flexible super-hydrophobic film and preparation method therefor
WO2018045621A1
Cited By
PVC (polyvinyl chloride) hard base material and preparation process thereof
CN121182096A
Super-hydrophobic marine protective coating with sharkskin structure based on laser etching and method thereof
CN121555037A